Magnetic fields modulate metabolism and gut microbiome in correlation with Pgc‐1α expression: Follow‐up to an in vitro magnetic mitohormetic study. Issue 8 (6th July 2020) - Tai, Yee Kit; Ng, Charmaine; Purnamawati, Kristy; Yap, Jasmine Lye Yee; Yin, Jocelyn Naixin; Wong, Craig; Patel, Bharati Kadamb; Soong, Poh Loong; Pelczar, Pawel; Fröhlich, Jürg; Beyer, Christian; Fong, Charlene Hui Hua; et al.
Abstract: Exercise modulates metabolism and the gut microbiome. Brief exposure to low mT‐range pulsing electromagnetic fields (PEMFs) was previously shown to accentuate in vitro myogenesis and mitochondriogenesis by activating a calcium‐mitochondrial axis upstream of PGC‐1α transcriptional upregulation, recapitulating a genetic response implicated in exercise‐induced metabolic adaptations. We compared the effects of analogous PEMF exposure (1.5 mT, 10 min/week), with and without exercise, on systemic metabolism and gut microbiome in four groups of mice: (a) no intervention; (b) PEMF treatment; (c) exercise; (d) exercise and PEMF treatment. The combination of PEMFs and exercise for 6 weeks enhanced running performance and upregulated muscular and adipose Pgc‐1α transcript levels, whereas exercise alone was incapable of elevating Pgc‐1α levels. The gut microbiome Firmicutes / Bacteroidetes ratio decreased with exercise and PEMF exposure, alone or in combination, which has been associated in published studies with an increase in lean body mass. After 2 months, brief PEMF treatment alone increased Pgc‐1α and mitohormetic gene expression and after >4 months PEMF treatment alone enhanced oxidative muscle expression, fatty acid oxidation, and reduced insulin levels. Hence, short‐term PEMF treatment was sufficient to instigate PGC‐1α‐associated transcriptional cascades governing systemic mitohormetic adaptations, whereas longer‐term PEMF treatment was capable of inducing related metabolic adaptations independently of exercise.